2005
DOI: 10.1063/1.1988978
|View full text |Cite
|
Sign up to set email alerts
|

Saturated domain switching textures and strains in ferroelastic ceramics

Abstract: This paper introduces saturated domain switching textures of three different ferroelastic ceramic crystal systems. The accompanying extrinsic domain switching strain is calculated exclusively using a volume-weighted integral of a single pole figure. In ceramics which are also ferroelectric, the electromechanical response is defined by the domain switching textures, strains, and strain asymmetry, which are found to be functions of the number and directions of possible ferroelastic structural distortions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
96
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(100 citation statements)
references
References 19 publications
3
96
1
Order By: Relevance
“…The higher degree of e D Tet is directly related to the large g Tet ($1.26% at E max ) that is approximately four times greater than the g Rh is $0.34%. 20 From the phase weighted calculated strain (green circles in Figures 3(c)-3(e)), it is evident that in the mixed phase BNT-7BT composition, extrinsic processes are the major contributors to the electric-field-induced strain, a result that is consistent with that reported for an MPB composition of Pb(Zr,Ti)O 3 . 48,49 The comparison of calculated total strain and measured macroscopic strain is shown in Figure 3(f).…”
Section: R3csupporting
confidence: 78%
See 1 more Smart Citation
“…The higher degree of e D Tet is directly related to the large g Tet ($1.26% at E max ) that is approximately four times greater than the g Rh is $0.34%. 20 From the phase weighted calculated strain (green circles in Figures 3(c)-3(e)), it is evident that in the mixed phase BNT-7BT composition, extrinsic processes are the major contributors to the electric-field-induced strain, a result that is consistent with that reported for an MPB composition of Pb(Zr,Ti)O 3 . 48,49 The comparison of calculated total strain and measured macroscopic strain is shown in Figure 3(f).…”
Section: R3csupporting
confidence: 78%
“…Quantification of microscopic origins from in situ diffraction data in different materials has been successfully conducted using selected reflection-fitting methods. [20][21][22][23][24] However, this method to quantify domain texture, lattice strain, and phase transformation strain for mixed-phase materials is difficult due to significant peak overlap. This difficulty can be overcome using full pattern Rietveld refinements.…”
mentioning
confidence: 99%
“…Previous researchers have calculated the theoretical maximum ε r /ε s for the rhombohedral and the tetragonal phases for electrical and mechanical loading. 37,38 It was found that the maximum ε r /ε s during compressive mechanical loading of polycrystalline samples that have an initial random orientation (i.e., untextured) was −0.269 and −0.285 for the tetragonal and rhombohedral phases, respectively. Here it was assumed that the single crystalline grains do not interact, must remain within their initial crystal phase (i.e., phase transitions were not allowed), have the same lattice distortion and retain it throughout loading, and are permitted to ferroelastically switch (i.e., no clamping effects, etc.).…”
Section: Model Simulations and Discussionmentioning
confidence: 99%
“…Generally, high Zr containing rhombohedral materials in both film and ceramic forms exhibit a higher ratio of switched unit cells than tetragonal ones. 44,45 This is in favor of a narrower spatial distribution of principal axes of the random dielectric tensor e ik which approaches a uniform tensor and, consequently, produces a more uniform spatial field distribution. The latter is described by a statistical field distribution as in Fig.…”
Section: B Comparison Of Switching In Ceramics and Oriented Thin Filmsmentioning
confidence: 99%